ANALISIS KELAYAKAN USAHA (STUDI KASUS WARUNG IKAN BANDENG BAKARDI KECAMATAN SEDATI KABUPATEN SIDOARJO) - Achmad Kaisi Amarco; Arga Christian Sitohang (CV. Denasya Smart Publisher, 2024)
This research aims to evaluate the potential success of grilled milkfish stalls in Sedati District, Sidoarjo Regency. The approach used in this research is a qualitative method by collecting data through observation and interviews. 6 informants were selected as research subjects to collect relevant data. The data collected includes initial capital, expenses and annual income. This data will be analyzed using the Net Benefit Cost Ratio (B/C Ratio), Revenue Cost Ratio (R/C Ratio), and Return On Investment (ROI) calculation tools. The results of calculations using this tool must exceed the number 1 (>1) so that the grilled milkfish stall in Sedati District, Sidoarjo Regency, is considered feasible to run. The results of the Revenue Cost Ratio (R/C Ratio) calculation will show how effective the income generated is in relation to the costs incurred.